1999
DOI: 10.1038/sj.cdd.4400476
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of caspase-3 in apoptosis

Abstract: Caspases are crucial mediators of programmed cell death (apoptosis). Among them, caspase-3 is a frequently activated death protease, catalyzing the specific cleavage of many key cellular proteins. However, the specific requirements of this (or any other) caspase in apoptosis have remained largely unknown until now. Pathways to caspase-3 activation have been identified that are either dependent on or independent of mitochondrial cytochrome c release and caspase-9 function. Caspase-3 is essential for normal brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

83
2,117
2
22

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,321 publications
(2,224 citation statements)
references
References 41 publications
83
2,117
2
22
Order By: Relevance
“…The severity of cardiac remodeling directly correlates with the rate and duration of pacing in pacing HF models,14 whereas it has been shown that cardiac apoptosis occurs rapidly after MI, and sustained apoptosis is associated with the extent of cardiac remodeling in HF models after MI 23, 24. To evaluate the extent of cardiac apoptosis in the ischemic HF model, we evaluated the protein expression of cleaved caspase 3 and caspase 3, which are essential for the apoptotic process 25. As a result, LAA in ischemic HF rabbits had a significantly higher activation of caspase 3 compared with that in control and HF‐RDN rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of cardiac remodeling directly correlates with the rate and duration of pacing in pacing HF models,14 whereas it has been shown that cardiac apoptosis occurs rapidly after MI, and sustained apoptosis is associated with the extent of cardiac remodeling in HF models after MI 23, 24. To evaluate the extent of cardiac apoptosis in the ischemic HF model, we evaluated the protein expression of cleaved caspase 3 and caspase 3, which are essential for the apoptotic process 25. As a result, LAA in ischemic HF rabbits had a significantly higher activation of caspase 3 compared with that in control and HF‐RDN rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we can suppose that cytochrome-c associates with Apaf-1 in the presence of dATP or ATP and induces its oligomerization [Hengartner, 2000]. Furthermore, the oligomeric Apaf-1 complex would recognize the inactive procaspase-9, forming the "apoptosome" [Porter and Janicke, 1999], which in turn induce autocatalytic processing of procaspase-9. Subsequently, the mature caspase-9 would activate its primary downstream target, procaspase-3, which can cleave some nuclear proteins such as PARP, leading to a typical apoptotic DNA fragmentation in multiples of 180-200 bp [Green and Kroemer, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…All caspases are synthesized as enzymatically inert zymogens and are activated by autocatalytic cleavage or by activation of other caspases. Among the various caspases, caspase-9 and caspase-3 appear to be important in apoptosis [Porter and Janicke, 1999;Kuida, 2000]. Activation of Bax and Bak results in the release of cytochrome-c from mitochondria Wei et al, 2001], which binds to Apaf-1 and promotes activation of procaspase-9, forming the apoptosome and resulting in caspase-9 activation [Li et al, 1997;Green and Reed, 1998].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their order in cell death pathways, caspases can be divided into initiator (caspase-2, -8, -9, and -10) and effector (caspase-3, -6, and -7) caspases. Among them, caspase-3, a member of the latter group, is absolutely crucial for apoptosis induction, as this enzyme is not only activated downstream of both the extrinsic and intrinsic death pathway, it is also responsible for the cleavage of the majority of substrates known so far [1,5]. More importantly, with the proteolysis of discrete substrates, caspase-3 evokes some of the typical morphological and biochemical alterations associated with apoptosis.…”
mentioning
confidence: 99%